Development of a framework to guide community engagement in paramedic education and training in the Western Cape - Moodley, Kubendhren (Division of Emergency Medicine, 2025)
Emergency Medical Services in South Africa provide healthcare to a vast array of culturally and socio-economically divided communities against the backdrop of slow economic growth, limited resource capacity, and high emergency care caseloads. In such settings, community engagement, as a key function of the higher education mandate, presents an opportunity for strengthening university-community partnerships for reciprocal benefits through undergraduate emergency medical care education. This study was conducted at five higher education institutions in the Western Cape Province, two of which offer emergency medical care qualifications. The objectives of the study were fivefold: (1) to establish the views of community engagement academics at higher education institutions regarding best practices on community engagement within health science education; (2) to ascertain how emergency medical care academics conceptualise community engagement and implement it within the context of teaching, learning and research (3) to explore the views of emergency medical care students about their experiences of community engagement; (4) to investigate the experiences of community engagement partners with regards to how they engage with emergency medical care students and academics from higher education institutions; and (5) to develop a framework to guide community engagement in emergency medical care, as an emerging health profession to effect positive change in its professional response to community engagement. This study employed an exploratory, descriptive qualitative research methodology. Semi-structured in-depth interviews and focus group interviews were utilised to collect the qualitative data. Study participants comprised academics from health science faculties with experience in community engagement, emergency medical care academics, paramedic students and community partners. The researcher sought to understand how the participants conceptualised community engagement, the values and principles underpinning community engagement, and what processes and activities can be used to advance community engagement at local universities. Through thematic analysis, six key themes emerged, which, together with supporting literature, served as a basis for developing a community engagement framework for emergency medical care education. The crucial structural elements of the developed community engagement framework were underpinned by a conceptual understanding of community engagement; the processes that fostered community engagement in health-related projects; the nature of community engagement projects in health sciences; and how the learning experiences of paramedic students could be enhanced. The framework is intended to guide emergency medical care academics to strengthen paramedic education with community engaged practices to ensure the development of socially responsive paramedic graduates while improving healthcare in impoverished communities through mutually beneficial university-community partnerships.